Different solid sample preparation methods affecting the spectral similarity of salmon calcitonin. Issue 5 (2010) - Lin, Shan-Yang; Lin, Chih-Cheng; Lee, Ting-Huei
Abstract : Salmon calcitonin (sCT) was selected as a model protein drug for investigating its structural similarity in the solid state by four sample preparation methods, such as tape, smeared, CaF2 and film methods. The conformational changes of sCT in the solid state were estimated by using a second-derivative Fourier transform infrared (FT-IR) microspectroscopy. The tape method was acted as a standard reference. The value of correlation coefficient ( r ) for smeared method was higher than that of other method, indicating that a novel technique by smearing sCT powder on the surface of KBr pellet was the best optimal sample preparation method.